Preparation and Evaluation of Intraperitoneal Long-Acting Oxaliplatin-Loaded Multi-Vesicular Liposomal Depot for Colorectal Cancer Treatment - Sharif Md Abuzar; Eun Jung Park; Yeji Seo; Juseung Lee; Seung Hyuk Baik; Sung-Joo Hwang (MDPI AG, 2020)
Colorectal cancer with peritoneal metastasis has a poor prognosis because of inadequate responses to systemic chemotherapy. Cytoreductive surgery followed by intraperitoneal (IP) chemotherapy using oxaliplatin has attracted attention; however, the short half-life of oxaliplatin and its rapid clearance from the peritoneal cavity limit its clinical application. Here, a multivesicular liposomal (MVL) depot of oxaliplatin was prepared for IP administration, with an expected prolonged effect. After optimization, a combination of phospholipids, cholesterol, and triolein was used based on its ability to produce MVL depots of monomodal size distribution (1-20 µm; span 1.99) with high entrapment efficiency (EE) (92.16% ± 2.17%). An initial burst release followed by a long lag phase of drug release was observed for the MVL depots system in vitro. An in vivo pharmacokinetic study mimicking the early postoperative IP chemotherapy regimen in rats showed significantly improved bioavailability, and the mean residence time of oxaliplatin after IP administration revealed that slow and continuous erosion of the MVL particles yielded a sustained drug release. Thus, oxaliplatin-loaded MVL depots presented in this study have potential for use in the treatment of colorectal cancer.